The concept of plato's theory of the allegory of the cave and its impact toward Malaysian current political scenario / Norun Najjah Ahmat and Siti Rohana Omar - Ahmat, Norun Najjah; Omar, Siti Rohana (2008)
Malaysian political scenario has changes a lot particularly after the shock and amazing (or could be considered as unbelievable) result of the current 12th election, which had occurred on 8 March 2008. Till now, the political situation is mess up and going to be messer; Barisan Nasional (BN) is in critical condition because they are divided among themselves, blame each others, the loosing support of the allied parties, but at the same time is trying hard to save the party and to kept it relevant to the recent political scenario. Meanwhile the united opposition party called Pakatan Rakyat (PR) is struggling to keep the collaboration stronger and alive after had been set up when the election end. Whatever political issues are happening in Malaysia, the scholars particularly the politicians or the academicians (political analyst) would recognize the deep-rooted impact of Plato's theory of the allegory of the cave toward the survival of the parties either opponent or government and its effect towards Malaysian political stability. This article aims to find the importance of the mentioned above theory of Plato and its impact on Malaysian current political situation